Study of FE (III) Hydroxide Polymaltose Complex to Correct Anemia in Cancer Patients - H.S, Pallavi; N.S, Nirzarini (Indian Journal of Pharmacy Practice)
Introduction: Anemia of cancer is characterized by ineffective erythropoiesis, which is due to a number of factors. One of the most important among these is abnormal iron metabolism. There is also 'functional failure' due to retention of iron in macrophages. Hence iron supplementation 2+ forms an important part for the treatment of anemia in cancer patients. Oral iron supplements, usually in the form of ferrous (Fe ) salts, are toxic to the gastrointestinal mucosa, leading to intolerance, resulting in poor compliance and failure of treatment. The sugar derivative maltose strongly 3+ chelates iron, and stabilizes in the less toxic ferric (Fe ) form. This chelated form of iron shows high bioavailability which eliminates the need for frequent dosing and therefore improves compliance. Materials and Method: This was a prospective, single centred, open label, nonrandomised study involving 20 patients of whom 17 completed the study. The patients were treated with ferric hydroxide polymaltose complex syrup (50mg/5ml) for 8 weeks. Results: At the end of 8 weeks, there was a significant increase in haemoglobin of the patients (from 9.41±1.24 to 10.92±0.91 g/dL, mean±s.d. P< 0.0001, paired t-test, t = 7.065, df = 16, confidence interval - 0.05.). Out of 17, 7 patients i.e. 41.18% showed a ≥ 2 g/dl rise in hemoglobin during or at the end of the treatment. Mean time required to achieve this rise in hemoglobin is found to be 7 weeks. Conclusion: The results demonstrate that Fe (III) hydroxide polymaltose complex is effective in improving hemoglobin levels in anemic cancer patients.
Keywords: Anemia; Iron deficiency anemia; Anemia of Cancer; Fe (III) Hydroxide Polymaltose complex